Macro-Level Determinants of Entrepreneurship and Endogeneity Bias – A Methodological Contribution - Brahim Gaies; Adnane Maalaoui (M@n@gement, 2022)
The eclectic theory of entrepreneurship has identified several macro-determinants of national entrepreneurial activities. Taking advantage of the availability of new databases, several recent empirical studies have sought to test these determinants in multicountry studies using multivariate regression models. Due to the lack of consensus around their results, this paper posits that this empirical literature may be subject to endogeneity bias, which seriously threatens its accuracy, consistency, and reliability, as well as the effectiveness of the resulting management and policy recommendations. Consequently, we methodologically demonstrate why and how endogeneity occurs in these studies by analyzing their empirical and theoretical models. We also provide a step-by-step guide to help researchers understand how to detect and correct endogeneity using IV techniques applied to a panel data analysis of the macro-determinants of early-stage entrepreneurship in a sample of 48 countries between 2000 and 2019. A ‘toolkit’ of generic STATA software commands specifying the tests, methods, and assumptions performed in this analysis is included. In doing so, we aim to raise awareness of endogeneity bias among researchers and to empirically guide future studies in order to avoid its hazards. Finally, after correcting for endogeneity, our analysis identifies the protection of property rights, entrepreneurial culture, income, and economic development as the most consistent macro-determinants of early-stage entrepreneurship, providing important policy and business insights.